Perrotta Autism Spectrum Disorders Questionnaire for infants and young adolescents (PASD-Qy) - Giulio Perrotta (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2022)
Building on the concept of "Autism Spectrum Disorder", as framed in the DSM-V, and taking up studies on the new etiological theory (PETA) focusing on the developmental model of the neurobiological matrix (PEMA) and related questionnaire (PTAS-Qa), in this research a new questionnaire is proposed that can focus on the presence or absence of 4 functional areas (interactional and movement, language, and communication, ideational and social, emotional and behavioral) and 25 type-deficit traits, grading the impairment according to a precise 5-level severity scale (PASSy). The new questionnaire (Perrotta Autism Spectrum Disorders Questionnaire for infants and young adolescents, PASD-Qy), is composed of 25 items, on a binary S/N scale and based on a total score of 10/10, for a population between 18 months and < 16 years, thus offering a structured view of the individual's cognitive organization, avoiding diagnostic fragmentations that might be inconsistent with the nosographic framework. By exemplifying the category, it is then possible to more easily frame the patient, who would thus be analyzed from a strictly functional point of view, also facilitating the preparation of therapeutic interventions, according to models already known in the literature (e.g., ABA), exactly as for the questionnaire dedicated to late adolescents and adults.